Effect of Cements at Different Temperatures on the Clinical Performance and Marginal Adaptation of Inlay-Onlay Restorations In Vivo - ÖZKAN, YASEMİN (WILEY-BLACKWELL, 2016)
Purpose: To evaluate the clinical performance of inlays and onlays luted with two different resin cements, mixed at different temperatures and to evaluate the marginal adaptation of the restorations. Materials and Methods: One hundred IPS e. max restorations (82 onlays, 18 inlays; 84 molars, 16 premolars) were placed in 50 patients (28 females, 22 males, mean age, 33 years). The restorations were assigned to six groups according to the luting agent temperature (25 degrees C, 37 degrees C, and 54 degrees C) and cement type (Variolink N high viscosity or G-Cem Automix). All restorations were evaluated after 1 week and 1 year by two examiners using modified USPHS criteria. Replicas of 30 selected onlay restorations (5 per group) were assessed for marginal quality under a scanning electron microscope (SEM) at 200x. Marginal adaptation was quantitatively evaluated in terms of percentage of gap formation, and marginal gap width was measured. Results: After 1 year, the total survival rates of the Variolink N high viscosity group and G-Cem Automix group were 100% and 93.8%, respectively. Three debondings occurred with the G-Cem Automix group, one from each temperature group. For 1-year clinical service time, no significant difference was noticed in the marginal adaptation of Variolink N high viscosity groups and the 37 degrees C G-Cem Automix group, while 25 degrees C and 54 degrees C G-Cem Automix groups' marginal adaptation scores decreased (p < 0.05). Regarding the SEM evaluations, Variolink N high viscosity cement groups showed better marginal adaptation than G-Cem Automix cement groups (p < 0.05). Cementation with the cements preheated to 37 degrees C increased continuous margins in both enamel-cement and cement-ceramic interfaces, but these results were not statistically significant (p > 0.05). Cements at different temperatures did not have significant effects on marginal gap widths of the restorations. Conclusions: The restorations cemented with Variolink N high viscosity cement mixed at the three tested temperatures exhibited better treatment options than the self-adhesive groups. Preheating the self-adhesive cement (G-Cem Automix) to 37 degrees C can be an effective method to have better marginal adaptation than the other self-adhesive groups (25 degrees C, 54 degrees C) tested in this study.
Keywords: Preheating; self-adhesive; SEM; inlay; onlay; clinical trial; CURED RESIN CEMENTS; ADHESIVE LUTING AGENTS; LUTE COMPOSITE ONLAYS; ALL-CERAMIC ONLAYS; BOND STRENGTH; SELF-ETCH; DENTIN; ENAMEL; CONVERSION; VITRO